The Critical Reading Experience of Abdelhamid Boraïo - MESSAOUDI, Sara (Journal of Ecohumanism, 2026)
This study aims to investigate the critical approach of Abdelhamid Bouraïo, who demonstrated a notable level of critical competence while engaging with Western critical methodologies. His critical discourse addressed a range of issues that emerged from his openness to Western criticism, particularly structuralism and semiotics. These issues underscored his remarkable capacity to activate and control the mechanisms inherent in these methodologies